Applications of Bacteriophages in the Treatment of Localized Infections in Humans - Morozova, Vera V.; Vlassov, Valentin V.; Tikunova, Nina V. (Frontiers in microbiology, 2018)
In the recent years, multidrug-resistant bacteria have become a global threat, and phage therapy may to be used as an alternative to antibiotics or, at least, as a supplementary approach to treatment of some bacterial infections. Here, we describe the results of bacteriophage application in clinical practice for the treatment of localized infections in wounds, burns, and trophic ulcers, including diabetic foot ulcers. This mini-review includes data from various studies available in English, as well as serial case reports published in Russian scientific literature (with, at least, abstracts accessible in English). Since, it would be impossible to describe all historical Russian publications; we focused on publications included clear data on dosage and rout of phage administration.